Dessulfurização de biogás por absorção em solução aquosa, auxiliado por resina de troca de ânions - Santos, Rosângela Aparecida Ribeiro (2023)
The quality of human life is directly linked to the availability of energy, and biogas is a renewable energy source that can be stored and is produced through waste. The main drawback of biogas is the presence of hydrogen sulfide (H2S), which corrodes installations and emits sulfur oxides (SOx) after combustion. Despite the existence of systems to remove H2S from biogas, there is a lack of systems for small and medium-sized rural properties and with an affordable implementation cost. In this work, the absorption of H2S from biogas in ultrapure water and in alkaline solution with 0.1 mol L-1 NaOH was studied, and the possibility of using these solutions to remove H2S from biogas was verified. The aqueous solutions resulting from the absorption of H2S from the biogas were treated with A400 ion exchange resin (Purolite®), seeking to regenerate the solution and recover the initial capacity to remove H2S from the biogas. The concentrations of H2S, which are in the form of sulfide at alkaline pH, were satisfactorily determined by a spectrophotometric analytical method, and confirmed the interaction of sulfide with the ion exchange resin by X-ray spectrometry coupled to a scanning electron microscope (EDS-SEM) . It was possible to verify that the biogas removal kinetics obeys the model proposed by Thomas, and by finding the kinetic parameters, it was possible to dimension a fixed bed containing A400 ion exchange resin (Purolite®) to treat the solutions saturated with H2S from the biogas. One can observe the technical viability of using an aqueous solution to absorb H2S, followed by regeneration with A400 and continuous reuse, considering the efficient removal of practically 100% of the H2S present in the solutions, and the possibility of using the absorbent solution in a closed system.